A systems biology approach to identify the key targets of curcumin and capsaicin that downregulate pro-inflammatory pathways in human monocytes. (December 2019) - Belenahalli Shekarappa, Sharath; Kandagalla, Shivananda; H Malojirao, Vikas; G.S, Pavan Kumar; B.T, Prabhakar; Hanumanthappa, Manjunatha
Graphical abstract: Highlights: A new robust systems biology approach was applied to identify target proteins (bottleneck) in monocyte VEGF signaling pathway. Evaluated the role of PMA and VEGF induced abnormal regulation of bottleneck proteins viz. ICAM1, Flt-1 and NF-κB in THP-1 cell lines. Drug target identified using systems biology approach was evaluated for anti-angiogenesis mechanism of curcumin and capsaicin in differentiated THP-1 cells (TAMs). Abstract: VEGFR1 (Flt-1), is a high-affinity tyrosine kinase receptor of VEGF found primarily on vascular endothelial cells. Recently, Flt-1 has shown to be expressed in human monocytes. However, the key intracellular signaling pathway mediated by Flt-1 receptor has been yet to be identified in monocytes. In this regard, using a robust systems biology approach, the key druggable target(s) involved in inflammatory angiogenesis mediated through VEGFR1 signaling was identified. Furthermore, experimental validation of key drug targets is conducted using PMA- and VEGF- stimulated human monocyte THP-1 cell lines. The key network pathways and corresponding disease modules were analyzed to identify the important biological processes perturbed in diseases. Using topological analysis, ICAM1 was identified as putative regulator of monocytes migration into tumor-micro environment. And these targets were examined by treating with curcumin and capsaicin molecules. Our results showed that these two molecules inhibited the over expression of targets such as ICAM1, Flt-1, and NF-κB in the VEGFR1 signalling pathway by reducing THP-1 chemotaxis. Besides, Curcumin and Capsaicin down-regulated expression of pro-inflammatory cytokines TNF-α, IL-6, and CXCL8/IL-8 and up regulated the expression of IL-10, a sign of lowered M1/M2 ratio relating to abrogation of inflammation.